Biomarkers associated with the development of comorbidities in patients with atopic dermatitis: A systematic review. Issue 1 (8th December 2022) - Broderick, Conor; Ziehfreund, Stefanie; van Bart, Karin; Arents, Bernd; Eyerich, Kilian; Weidinger, Stephan; Rastrick, Joseph; Zink, Alexander; Flohr, Carsten; ,
Abstract: Biomarkers associated with the development of comorbidities in atopic dermatitis (AD) patients have been reported, but have not yet been systematically reviewed. Seven electronic databases were searched, from database inception to September 2021. English language randomized controlled trials, prospective and retrospective cohort, and case–control studies that investigated the association between a biomarker and the development of comorbidities in AD patients were included. Two authors independently screened the records for eligibility, one extracted all data, and critically appraised the quality of studies and risk of bias. Fifty six articles met the inclusion criteria, evaluating 146 candidate biomarkers. The most frequently reported biomarkers were filaggrin mutations and allergen specific‐IgE. Promising biomarkers include specific‐IgE and/or skin prick tests predicting the development of asthma, and genetic polymorphisms predicting the occurrence of eczema herpeticum. The identified studies and biomarkers were highly heterogeneous, and associated with predominately moderate‐to‐high risk of bias across multiple domains. Overall, findings were inconsistent. High‐quality studies assessing biomarkers associated with the development of comorbidities in people with AD are lacking. Harmonized datasets and independent validation studies are urgently needed.